Assessment of Some Characteristics and Properties of Zirconium Dioxide Nanoparticles Modified with 3-(Trimethoxysilyl) Propyl Methacrylate Silane Coupling Agent - Phi Hung Dao; Thuy Chinh Nguyen; Thi Lan Phung; Tien Dung Nguyen; Anh Hiep Nguyen; Thi Ngoc Lan Vu; Quoc Trung Vu; Dinh Hieu Vu; Thi Kim Ngan Tran; Hoang Thai (Journal of Chemistry)
This study presents the results of surface modification of zirconium dioxide (ZrO2) nanoparticles by 3-(trimethoxysilyl) propyl methacrylate silane coupling agent by assessing some characteristics and properties of modified ZrO2 nanoparticles by infrared spectroscopy, thermogravimetric analysis, size distribution, zeta potential, and field emission scanning electron microscopy methods. The modified and unmodified ZrO2 nanoparticles have been used as nanoadditives for organic coatings based on acrylic emulsion resin. The abrasion resistance of acrylic coating was evaluated according to ASTM E968-15. The obtained results show that ZrO2 nanoparticles were functionalized successfully with 3-(trimethoxysilyl) propyl methacrylate silane. The modified ZrO2 nanoparticles exhibit a positive effectiveness in the enhancement of the abrasion resistance of acrylic resin coating compared to unmodified ZrO2 nanoparticles.